Recent developments and applications of capillary electrophoresis with laser-induced fluorescence detection in biological samples - Ban, Eunmi; Song, Eun Joo (ELSEVIER, 2013)
Since the human genomic project, the analysis of biomolecules using biotechnology and biopharmaceuticals has become increasingly important for the investigation of molecular mechanisms of biological processes and disease, as well as for the discovery of new biomarkers and drug targets. Among a number of analytical tools and technologies, capillary electrophoresis (CE) is emerging as a useful analytical tool for analyzing various biomolecules, as well as for performing genome sequencing in biological studies because of the simple sample preparation involved in the method and the efficient resolution of compounds of various sizes. In particular, CE with laser-induced fluorescence (CE-LIF) detection is a promising and relatively rapidly developing tool with the potential to provide a highly sensitive and specific analysis of biological molecules. This paper gives a short overview of the methodological and instrumental developments and applications of microchip-based CE and CE-LIF for the analysis of DNA, RNA, proteins, and peptides in the past 3 years (C) 2013 Elsevier B.V. All rights reserved.
Keywords: SQUARYLIUM CYANINE DYE; CE-LIF; GEL-ELECTROPHORESIS; MICROCHIP ELECTROPHORESIS; SIEVING ELECTROPHORESIS; QUANTITATIVE-ANALYSIS; ZONE-ELECTROPHORESIS; MICRORNA DETECTION; MASS DETECTION; BORONIC ACID